Organizational report cards - Gormley, William T., Jr., 1950- (Harvard University Press, 1999)
In recent years, consumers, professional organizations, government officials, and third-party payers have become increasingly concerned about how to assess the quality of the services provided by organizations in both the private and the public sectors. One new approach is the organizational report card, which compares the performance of organizations such as public schools, colleges, hospitals, and HMOs. This book offers the first comprehensive study of such instruments. It discusses the circumstances under which they are desirable alternatives to other policy instruments, such as regulation; how they should be designed; who is likely to use them and for what purpose; and what role, if any, government should have in their creation. Informed by cases drawn from education, health, and other policy areas, this book develops a conceptual framework for analyzing these issues. It explores the tradeoffs in measuring performance, the methods of communicating results effectively to mass and elite audiences, and the ways in which organizations respond to the data gathered.